2019
DOI: 10.3390/ijms20163910
|View full text |Cite
|
Sign up to set email alerts
|

From Green Remediation to Polymer Hybrid Fabrication with Improved Optical Band Gaps

Abstract: The present work proposed a novel approach for transferring high-risk heavy metals tometal complexes via green chemistry remediation. The method of remediation of heavy metals developed in the present work is a great challenge for global environmental sciences and engineering because it is a totally environmentally friendly procedure in which black tea extract solution is used. The FTIR study indicates that black tea contains enough functional groups (OH and NH), polyphenols and conjugated double bonds. The sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 88 publications
(147 reference statements)
6
73
0
Order By: Relevance
“…Obviously, only the hump from 2θ = 59 • to 2θ = 67 • can be observed. Other researchers observed such humps for organometallic materials [80]. Therefore, XRD analysis results authenticate that reaction takes place between the PI polymer and the synthesized organosilver material.…”
Section: X-ray Diffractionsupporting
confidence: 66%
“…Obviously, only the hump from 2θ = 59 • to 2θ = 67 • can be observed. Other researchers observed such humps for organometallic materials [80]. Therefore, XRD analysis results authenticate that reaction takes place between the PI polymer and the synthesized organosilver material.…”
Section: X-ray Diffractionsupporting
confidence: 66%
“…To overcome these issues, the addition of Cd(II)–complex and Gly to the PE were attempted to improve the structure of amorphous PE and σ DC . The nature of amorphous PE in the electrolyte system was expanded with the insertion of metal complexes and Gly [ 14 , 17 ]. The Gly incorporation into the system of polymer and salt assists salt dissociation, which consequently reduces the salt recrystallization occurrence.…”
Section: Resultsmentioning
confidence: 99%
“…Previous study indicated that the XRD pattern of the Cu(II)-complex is almost amorphous, therefore, crystalline peaks were not detected within the entire 2θ degrees. Noticeably, a hump only was observed from 2θ = 20° to 30° [ 14 ]. XRD analysis results confirm that complexation takes place between the PVA and electrolyte components.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations